Financial Responsibility for Out-of-Wedlock Children by Underage Parents: An Islamic Law and Indonesian Legislative Perspective - handayani, Puji Tri; Nurhayati, Agustina; Pradikta, Hervin Yoki (Nizham Jurnal Studi Keislaman, 2025)
Out-of-wedlock pregnancies involving underage parents create complex legal, social, and moral challenges, particularly concerning the financial responsibility for children born from such relationships. This issue is crucial, as out-of-wedlock children constitute a vulnerable group entitled to legal protection, including the fulfillment of their basic needs, while underage parents do not yet possess full legal capacity. This study employs a normative juridical method with statutory, conceptual, and comparative approaches. The findings reveal that under Islamic law, financial responsibility for out-of-wedlock children is normatively borne by the mother, as there is no recognized lineage (nasab) with the biological father. Meanwhile, Indonesian legislation—through Constitutional Court Decision No. 46/PUU-VIII/2010—has opened the possibility of establishing a civil relationship between an out-of-wedlock child and the biological father, including the obligation to provide financial support. This study recommends strengthening regulations and developing a more responsive family law model that upholds children’s rights while considering the sociological conditions of underage parents.